Analysis of anaerobic digestion process for biogas production using aspen plus - Muhammad Alif Imran, Chek Azam; Noorlisa, Harun (2021)
Municipal solid waste (MSW) is solid waste comprising all household waste and non-hazardous waste (food waste 60%,paper 21%, plastic 12%, glass 5% and others 2%). Anaerobic digestion (AD) is the series of biological process where microorganism break down biodegradable materials without having the oxygen to produce biogas. Food waste contribute more moisture , suitable for Anaerobic Digestion process (H. Ma et al., 2009).